The evaluation of forestry ecological security in China: Developing a decision support system. (August 2018) - Lu, Shasha; Li, Junpu; Guan, Xingliang; Gao, Xianjun; Gu, Yanhong; Zhang, Dahong; Mi, Feng; Li, Dandan
Graphical abstract: Highlights: A decision support system for forestry ecological security evaluation was developed. It considers multiple factors within a general decision-support framework to calculate the forestry ecological security index and its three subsystems at national and provincial level. The forestry ecological security condition of China illustrates an upward trend along with some fluctuations from 1999 to 2012 and presents significant spatial differences. Abstract: The development of modern science and technology tends to accompany environmental crisis and ecological degradation. And the evaluation of the security condition of the forestry ecosystem has become an urgent task. This paper details the development of a decision support system (the FESEDSS), which was built to provide a range of actors with an effective tool for the evaluation and governance of forestry ecological security in China. The FESEDSS considers multiple factors through a general decision-support framework, making possible the calculation of ecological security indexes and relative indexes for the forestry ecosystem and its three subsystems (forest, wetlands and desert) at both the national and provincial level. The system integrates econometric models, mathematical methods, geographic information systems and a dynamic database, providing users with an understanding of spatiotemporal patterns and regional differences in the ecological security of the forestry ecosystem and its three subsystems in China's 31 provinces. Results generated using the FESEDSS and addressing the period 1999–2012 demonstrate a positive change in forest ecological security condition and a negative change in wetland and desert ecological security. Spatially, the ecological security of the forest subsystem was shown to have improved significantly in eastern and central China, while in the western region it experienced degradation. The ecological security of wetland ecosystems performed well in the southwest region and the middle and lower reaches of the Yangtze River; and desert ecological security was shown to be of a higher standard in south of Qinling-Huaihe Line than in the northern regions of the country. The overall forestry ecological security condition (which integrates the three subsystems) demonstrated an upward trend with some fluctuations, with high values generally being located in the south and low values in the north of the country. Finally, the paper also discusses performance, uncertainty, and implementation challenges, as well as detailing potential extensions of the FESEDSS. The paper lays a foundation to the national forestry ecological security evaluation and monitoring.